A welfare analysis of non participation in an export quota scheme: The case of importing countries - Roland Herrmann (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1986)
It has been largely ignored in the commodity stabilization literature that export quota schemes can cause a co-existence between a controlled and an uncontrolled market. This article analyzes the welfare implications of such a scheme on non-participating importing countries. The determinants of the welfare effects are elaborated. It is shown that non-participation in the export quota scheme may increase or decrease the importing countries' welfare compared to the situation of a liberalized world market. Magnitude and sign of the welfare impacts are shown to depend crucially on the rigidity of the quota policy. From the individual importing country's point of view, it is derived that non-participation instead of entering the agreement may raise national welfare, even if the export quota policy lowers its welfare level compared to a free trade situation.
Keywords: 330; Rohstoffabkommen; Wohlfahrtstheorie